Muhammad Amin Al-Shinqiti and the Idea of Economic Equity in the Qur’an - Anjani I'anatul Maula; Fejrian Yazdajird Iwanebel (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This paper delves into the exploration of economic principles within Qur’anic exegesis. The focus centers on the elucidation of economic equity by, Muhammad Amin al-Shinqiti, as expounded in his tafsir “Adwa’ al-Bayan fī Idah al-Qur’an bi al-Qur’an.” A key emphasis is placed on al-Shinqiti’s comprehensive analysis of economic equity within Surah al-Hasyr [59]: 7. Additionally, al-Shinqiti contextualizes the verse to argue that the booty (al-fay’), as mentioned in the verse, should be reclaimed and channeled into state revenues. Employing Hassan Hanafi’s social hermeneutics framework, this article draws the conclusion that al-Shinqiti critically evaluates both capitalist and socialist economic theories. Al-Shinqiti, through his interpretation, asserts that the fundamental essence of the verse is the eradication of favoritism, thus propelling the attainment of economic equity. Al-Shinqiti distinguishes economic equality from economic equity, contending that the former is an unattainable objective. Furthermore, he advocates for an Islamic economic system characterized by a limited free economy, impartial distribution of state resources, and a focus on the comprehensive welfare of society. This exploration sheds light on Al-Shinqiti’s nuanced perspective on economic principles and provides valuable insights into the Islamic economic framework.